BRAC annual report, 2004 - BRAC (© BRAC, 2016)
1. Mission statement 2. Acronyms 3. Map 4. BRAC at a Glance 5. Timeline 6. Overview 7. Chairperson's statement 8. Disaster: are we ready for the next one? 9. Rahima: a life of struggle & overcoming odds 10. Voices of silenced women 11. The story of an ordinary boy with extraordinary dreams 12. Economic Development Programme 13.Social Development, Human rights and legal services programme 14. Health programme 15. Education programme 16. Support programmes 17. BRAC Afghanistan 18. Governance 19. Management 20. Organogram 21. Audit report